COMPARATIVE ANALYSIS OF MANUAL AND DIGITAL SOUNDING ON DIESEL FUEL STOCK ACCURACY AT PT. BRAHMA BINA BAKTI KARET - Abdi Argani; Tuty Ningsih (LPPM Universitas Malikussaleh - Indonesia, 2026)
This study aims to analyze the comparison of manual and digital sounding methods on the accuracy of diesel fuel (BBM) stock at PT. Brahma Bina Bakti Karet. The development of sensor-based digital technology and the Internet of Things (IoT) encourages the use of automatic measurement systems that are considered more efficient and accurate than manual methods. This study uses a comparative quantitative approach with a field experiment design, where both methods are applied to the same tank at almost the same time. The data analyzed include fuel volume and measurement time, then compared with reference data from the SAP system. The results show that the manual method produces an average volume of 1,267 liters with a difference of 301 liters and a time of 205 seconds, while the digital method produces an average volume of 1,269 liters with a difference of 303 liters and a time of 5 seconds. The results of the paired t-test show a significance value of 0.000 < 0.05, which means there is a significant difference between the two methods. Although the level of accuracy is relatively the same, the digital method is superior in time efficiency and consistency of results, making it more effective in fuel stock management. Keywords: Manual Sounding, Digital Sounding, Accuracy, Time Efficiency, Diesel Fuel